Reproductive performance and mineral profile of postpartum fertile and infertile Surti buffaloes - KHASATIYA, C T; DHAMI, A J; RAMANI, V P; SAVALIA, F P; KAVANI, F S (The Indian Journal of Animal Reproduction, 2023)
The reproductive performance and plasma profile of macro-micro-minerals was studied in fertile (n=l2) andinfertile (n= 11) Surti buffaloes at weekly interval from the day of calving till 15 weeks postpartum. The occurrence of firstoestrus, service period and calving interval were significantly shorter (P < 0.01) in fertile than the infertile buffaloes. Thepooled mean plasma levels of calcium, inorganic phosphorus and magnesium in fertile and infertile groups of buffaloes were10.21±0.16 and 10. 15±0. I 7 mg/di; 6.23±0.19 and 6.35±0.21 mg/di, and 3.86±0.08 and 3. 70±0.09 mEq/1, respectively,which neither varied significantly between groups nor between weeks postpartum. The overall mean plasma iron, copperand manganese levels in fertile and infertile groups of buffaloes were found to be almost identical between groups (3.48±0.11vs 3.69:t0. I I; 1.44:t0.03 vs 1.43±0.03 and 0.08:t0.01 vs 0.ll:!:0.01 ppm, respectively) whereas the mean zinc level wassignificantly higher (1.95±0.06 vs 1.66:t0.06 ppm) and cobalt lower (0.52:t0.02 vs 0.61±0.02 ppm) in infertile than thefertile group. The weekly profile for any of these traits did not vary significantly in any of the groups. The plasma calciumhad significant negative correlation with phosphorus (-0.71, -0.62) in both fertile and fertile groups, and with Cu (-0.62),postpartum first oestrus, service period and calving interval (-0.67, -0.74, -0.74) only in fertile group. Inorganic phosphorusand magnesium did not show significant correlation with any of the traits. Amongst trace minerals, significant correlationswere observed for Mn with Zn (0.61); and Cu with service period and calving interval (0.65, 0.63), and Fe with uterineinvolution (0.59) only in fertile group.
Keywords: Blood plasma; fertility status; macro-micro minerals; postpartum period; Surti buffalo